UAV cooperative decision and control : challenges and practical approaches - Shima, Tal; Rasmussen, Steven J. (Society for Industrial and Applied Mathematics (SIAM, 3600 Market Street, Floor 6, Philadelphia, PA 19104), 2009)
Unmanned aerial vehicles (UAVs) are increasingly used in military missions because they have the advantages of not placing human life at risk and of lowering operation costs via decreased vehicle weight. These benefits can be fully realized only if UAVs work cooperatively in groups with an efficient exchange of information. This book provides an authoritative reference on cooperative decision and control of UAVs and the means available to solve problems involving them.
Keywords: Drone aircraft -- Control systems.; Drone aircraft -- Automatic control.; Task analysis.; Decision making.; Job analysis.; elektronické knihy; electronic books